The Position of Customary Criminal Law in Law No. 1 of 2023 on the Criminal Code - Maulana Halim Putra; Rizanizarli, Rizanizarli; Sulaiman, Sulaiman (International Journal of Law and Society, 2025)
Law Number 1 Year 2023 on the Criminal Code (KUHP) is a form of national criminal law reform that recognises the existence of customary criminal law. However, it has not been regulated in detail how the implementation and position of customary criminal law as a reason for criminal prosecution, and there are fundamental differences between the two concepts of the legal system. The problems in this research are how the position between customary criminal law and national criminal law in the new Criminal Code, how the legal certainty of the regulation of customary criminal law in the new Criminal Code, and how the challenges in enforcing customary criminal law using the current criminal justice system in Indonesia. This research uses normative juridical method with regulatory and conceptual approaches. The results show that the applicability of customary criminal law is limited to the area where the law lives and applies to customary criminal acts committed in the area where the law lives. The position of customary criminal law can be valid as a reason for criminal prosecution if the customary law that is still alive in the community has been stipulated in the form of Regional Regulations, and customary offences that are similar to offences in the New Criminal Code will be ruled out, and the classification of customary sanctions as additional sanctions, positioning customary penalties to be complementary or secondary, because additional sanctions can only be imposed together with the main sanctions. Legal certainty towards the regulation of customary criminal law is highly dependent on the formulation of the elements of each offence of customary criminal law stipulated in regional regulations. The current criminal justice system in Indonesia (KUHAP) cannot realise the objectives of customary criminal law. The objectives, characteristics, and procedures in the concept of customary law are contrary to those in the criminal justice system. Restorative Justice can be utilised as an alternative to the settlement of customary criminal cases when the New Criminal Code comes into effect.